The Effect of Self-Esteem and Self-Efficacy on Employee Performance, with Job Satisfaction as a Mediator (Study at PT Perkebunan Nusantara IV Regional VII) - Shafa Karseva; Zainnur M. Rusdi; Luthfi Firdaus (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to determine the influence of self-esteem and self-efficacy on employe performance, with job satisfaction as a mediator, at PT Perkebunan Nusantara IV Regional VII. The research method uses a quantitative approach with a survey technique thru questionnaires distributed to 158 respondents. Data analysis was performed using multiple linear regression. Hypothesis testing will be conducted using the Bootstrapping method with the PROCESS Macro Hayes extension for the SPSS program. The research results indicate that self-esteem has a direct positive and significant effect on employe performance at PT Perkebunan Nusantara IV Regional VII. Self-efficacy has a direct positive and significant effect on employe performance at PT Perkebunan Nusantara IV Regional VII. Job satisfaction mediates the influence of self-esteem on employe performance at PT Perkebunan Nusantara IV Regional VII. Additionally, job satisfaction mediates the influence of self-efficacy on employe performance at PT Perkebunan Nusantara IV Regional VII.